2005
DOI: 10.1144/1467-7873/03-061
|View full text |Cite
|
Sign up to set email alerts
|

The design and application of sequential extractions for mercury, Part 1. Optimization of HNO 3 extraction for all non-sulphide forms of Hg

Abstract: The final step in a sequential extraction procedure for Hg in geological samples usually involves a strong acid attack such as aqua regia. It is assumed that the Hg component measured in this step represents HgS (cinnabar), the common and highly insoluble form of Hg in nature. This paper describes the optimization of an HNO 3 -based dissolution of all non-sulphide forms of Hg while minimizing the solubilization of HgS. Previous work indicated that 12M (75% v/v) HNO 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…From the results of the sequential extraction of BPL, it appears that the Hg chemisorbed to thiophene is removed at step 5. As well, it is known that BPL also retains mercury by adsorption of the elemental form [6] and it is well established that physically adsorbed elemental mercury is very selectively extracted by step 5 [11]. These two forms of sorbed mercury are probably the main types found in BPL in addition to minor amounts of mercury sulfide.…”
Section: Sequential Extractionmentioning
confidence: 93%
See 1 more Smart Citation
“…From the results of the sequential extraction of BPL, it appears that the Hg chemisorbed to thiophene is removed at step 5. As well, it is known that BPL also retains mercury by adsorption of the elemental form [6] and it is well established that physically adsorbed elemental mercury is very selectively extracted by step 5 [11]. These two forms of sorbed mercury are probably the main types found in BPL in addition to minor amounts of mercury sulfide.…”
Section: Sequential Extractionmentioning
confidence: 93%
“…Since it is thought that much of the mercury captured by sulfurimpregnated activated carbon is in the form of particles of HgS, it is essential to be able to reliably distinguish this phase from elemental Hg either physically adsorbed or chemisorbed onto the surface of the carbon. The GSC study showed that a 2 h extraction using 40% HNO 3 in a mechanical shaker followed by a rinse was able to dissolve all non-sulfide forms of Hg, including adsorbed elemental Hg, without solubilizing HgS even when present as very fine particles of a few micrometers or less [11].…”
Section: Introductionmentioning
confidence: 99%
“…The extracts were then filtered in parallel using 0.45-µm PTFE, 0.22-µm PTFE, and 0.02-µm Whatman ® Anotop ® alumina syringe filters, and stabilized by BrCl addition. To test the influence of time on extracted Hg, the same three soil samples were extracted for varying time periods on an end-over-end shaker (1,6,24,48,72,96, and 168 h), centrifuged, filtered using 0.45-µm PTFE syringe filters, and stabilized by BrCl addition. The Hg and Fe, S, and Mn concentrations in all batch extraction solutions were measured using CV-AFS and ICP-OES as described above, respectively.…”
Section: Methyl-hg Analysismentioning
confidence: 99%
“…To evaluate the mobility of mercury, many studies have been done on soil and sediment samples (Biester and Scholz 1997;Barnett and Turner 2001;Kot and Matyushkina 2002;Bloom et al 2003;Sahuquillo et al 2003;Kot 2004;Hall et al 2005;Sanchez et al 2005;Shi et al 2005b). The use of sequential extraction procedures to characterize mercury into different chemical fractions is a popular method in these studies, and the fractions represent different physical and chemical forms of mercury (Sahuquillo et al 2003;Hall et al 2005;Shi et al 2005a;Noel et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The use of sequential extraction procedures to characterize mercury into different chemical fractions is a popular method in these studies, and the fractions represent different physical and chemical forms of mercury (Sahuquillo et al 2003;Hall et al 2005;Shi et al 2005a;Noel et al 2007). Even though the methodology has been applied to many different samples, there are few applications to coal (He et al 2006;Zheng et al 2008).…”
Section: Introductionmentioning
confidence: 99%